Effects of organic extracts of six Bangladeshi plants on in vitro thrombolysis and cytotoxicity - Rahman M Atiar; Sultana Rabeya; Bin Emran Talha; Islam M Saiful; Rahman M Ashiqur; Chakma Joti Sankhar; Rashid Harun-ur; Hasan Chowdhury Mohammad Monirul (BMC, 2013)
Abstract Background Thrombus formed in blood vessels lead to atherothrombotic diseases such as myocardial or cerebral infarction. Thrombolytic agents are used to dissolve the already formed clots in the blood vessels; however, these drugs sometimes cause serious and fatal consequences. Herbal preparations have been used since ancient times for the treatment of several diseases although they show little toxicity in some cases. Aqueous extracts of herbs used in thrombolysis have been reported before with cytotoxic data, however, the organic extracts of herbs have not been documented. This study aims to investigate whether organic extracts possess thrombolytic properties with minimal or no toxicity. Methods An in vitro thrombolytic model was used to check the clot lysis effect of six Bangladeshi herbal extracts viz., Ageratum conyzoides L., Clausena suffruticosa, Leea indica (Burm.f.) Merr., Leucas aspera Willd., Senna sophera L. Roxb., and Solanum torvum Swartz. using streptokinase as a positive control and water as a negative control. Briefly, venous blood drawn from twenty healthy volunteers was allowed to form clots which were weighed and treated with the test plant materials to disrupt the clots. Weight of clot after and before treatment provided a percentage of clot lysis. Cytotoxicity was screened by brine shrimp lethality bioassay using vincristine sulfate as positive control. Results Using an in vitro thrombolytic model, Ageratum conyzoides, Clausena suffruticosa, Leea indica, Leucas aspera, Senna sophera and Solanum torvum showed 18.12 ± 2.34%, 48.9 ± 2.44%, 39.30 ± 0.96%, 37.32 ± 2.00%, 31.61 ± 2.97% and 31.51 ± 0.57% and clot lysis respectively. Among the herbs studied Clausena suffruticosa, Leea indica and Leucas aspera showed very significant (p < 0.0001) percentage (%) of clot lysis compared to reference drug streptokinase (75.00 ± 3.04%). In brine shrimp cytotoxic assay, the extracts Ageratum conyzoides, Clausena suffruticosa, Leea indica, Leucas aspera, Senna sophera and Solanum torvum showed LC50 values 508.86 ± 6.62,41.16 ± 1.26, 2.65 ± 0.16, 181.67 ± 1.65, 233.37 ± 7.74 and 478.40 ± 3.23 μg/ml, respectively, with reference to vincristine sulfate (LC50 0.76 ± 0.04). Conclusion Through our study it was found that Clausena suffruticosa, Leea indica and Leucas aspera possessed effective thrombolytic properties whereas Senna sophera and Solanum torvum showed moderate to mild thrombolytic effects while Ageratum conyzoides showed no significant effect. No extract was found cytoxic compared to positive control. Clausena suffruticosa, Leea indica and Leucas aspera could be incorporated as a thrombolytic agent with in vivo effects to improve the atherothrombotic patients. However, Clausena suffruticosa could be the best one to use in this purpose.